PEMILIHAN PEMASOK BERKELANJUTAN DALAM INDUSTRI 4.0 DI PT.XYZ - Monica Permatasari, (2021)
PT XYZ is one of the automotive companies in Indonesia, there are complaints of delays in the supply of materials to PT XYZ in 2019-2020 about 15% of the total fleet issued. Delays that occur result in loss of turnover. PT XYZ only assesses subjectively based on price, quality, delivery, and safety. Therefore, the need for more comprehensive and objective considerations according to company needs. In this research, the Analytic Network Process (ANP) method is used to weight the criteria and test the level of consistency of the pairwise comparison matrix and if the matrix is consistent, it will be continued with the Technique for Others Reference by Similarity to the method. Ideal Solution (TOPSIS) to rank and determine the selected alternative supplier by using the criteria weight input decision-making. There are 3 perspective criteria, namely: economic, environmental, and social and 12 sub-criteria the highest weight economic criteria is quality and the lowest is environmental reliability, the highest weight is waste handling and the lowest weight is green design ability, the social criteria is the highest weight is complying with policies and the lowest is support for the local community. The priority order of suppliers for raw materials at PT. X includes supplier A with a preference value of 0.81, supplier B of 0.36, and supplier C with the lowest value of 0.34 but the need for additional criteria and sub-criteria so that the accuracy level in the selection of alternative suppliers at PT X increases